Power Failure Detection System and Intimation over Internet - V.Saritha; A.Ramashankar; K.Laxmiprasanna; P.Suma; S.Gouthami (International Journal of Engineering and Management Research, 2021)
Electricity is a crucial and necessary aspect of modern life. Electricity is used to power appliances, computers, electronics, machinery, and public transportation systems, as well as for lighting, heating, cooling, and refrigeration. When the electricity goes out, understanding what caused it can help you predict when it will be restored. The weather is the primary cause of power outages. Human mistake, equipment failure, and scheduled maintenance could all be factors. As a result, we're using this project to detect power outages and notify users via a connected smartphone notification.